Agri-Processing and Developing Countries - Wilkinson, John; Roch, Rudi (World Bank, Washington, DC, 2012)
The importance of the agri-processing sector for developing countries is assessed in the light of two distinct trends. First, processed products now predominate global food trade, which is the case for both developing country exports and imports. Second, there has been significant change in the composition of food exports from developing countries, with "non-traditional exports" leading the way. These exports provide new opportunities for development strategies, though least developed countries have shifted from being net food exporters to net importers predominantly of processed products. This report presents a statistical profile of the food-processing sector in developing countries. Common to most analyses is the identification of new patterns of coordinating food supply chains in response to higher and differentiated quality and health standards and more complex logistical requirements. Also discussed are the policy implications if the food-processing sector of developing countries is to become a strategic lever for dynamic growth.